Low Protein-High Carbohydrate Diets Alter Energy Balance, Gut Microbiota Composition and Blood Metabolomics Profile in Young Pigs - Shelby Spring (Nature Portfolio, 2020)
Abstract Reducing dietary crude protein (CP) beyond a certain threshold leads to poor growth performance in pigs; however, the underlying mechanisms are not well understood. Following an adaption period, thirty-seven weaned pigs were weight matched (8.41 ± 0.14 kg), housed individually and randomly assigned into three groups with different dietary CP levels: 24% CP (CON; n = 12), 18% CP (n = 12) and 12% CP (n = 13) for 28 days. The body weight was not different between the CON and 18% CP diets, but 12% CP significantly decreased body weight after day 21. Compared to the CON, pigs fed with 12% CP decreased feed intake day 17 onwards. The 12% CP diet increased the energy expenditure during week 1 compared to the CON. The 12% CP influenced starch and sucrose, nitrogen, and branched-chain amino acids metabolism pathways. The feces of pigs fed with 12% CP were less enriched in Prevotella, but had higher relative abundance of Christensenedilaceae, Aligiphilus and Algoriphagus than CON and 18% CP. Overall, reducing dietary CP by 50%, but not by 25%, significantly influenced the physiological responses in nursery pigs. The pigs fed with low or standard protein diets had differential bacterial communities in their feces as well as serum metabolomics profile.